Phymatosorus grossus (Polypodiaceae) in Mexico and comments on other non-native pteridobionts - Tejero-Díez, J. Daniel; Torres-Díaz, Alin N. (Instituto de Ecología, A.C., 2012)
Phymatosorus grossus (Langsd. & Fisch.) Brownlie is reported for Mexico for the first time. It is an exotic fern that presents characteristics typical of invasive species. We give a morphological description, ecological features and distribution of the species. We also include a list of other non-native clubmosses and ferns reported in the literature, as well as other species of pteridophytes that have probably arrived in Mexico recently.